Role Of Artificial Intelligence Adoption, Self Confidence, And Information Quality In Increasing E-Commerce Adoption And Marketing Performance Of Msmes In Palopo City - Praginata, Ratu Dhita; Solling Hamid, Rahmad; Maszudi, Edi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze how the adoption of Artificial Intelligence (AI), self-confidence, and information quality influence the adoption of e-commerce and the marketing performance of Micro, Small, and Medium Enterprises (MSMEs). Methodology: The research employed a survey method involving 222 MSME respondents in Palopo City. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach, which is appropriate for evaluating complex inter-variable relationships and hypothesis testing. Results: The findings demonstrate that AI adoption, self-confidence, and information quality each have significant effects on e-commerce adoption and, subsequently, on marketing performance. AI enables automation and personalization; self-confidence drives willingness to adopt innovation; and high-quality information supports better decision-making. Findings: The study reveals that these three variables act as enablers of digital transformation for MSMEs, particularly in strengthening their marketing competitiveness through e-commerce. Novelty: This research integrates psychological (self-confidence), technological (AI adoption), and informational dimensions into a single predictive model for MSME digital adoption. Originality: The study offers a comprehensive approach to understanding MSMEs' readiness for e-commerce in a developing region, a topic still underexplored in empirical literature. Conclusion: Adopting AI, fostering self-confidence, and ensuring quality information are key to enhancing e-commerce use and marketing outcomes in MSMEs. Type of Paper: Empirical research paper.